Lessons learned about conspiracy mindset and belief in vaccination misinformation during the COVID pandemic of 2019 in the United States - Romer, Daniel; Jamieson, Kathleen H. (Frontiers in Communication, 2025)
We review research we conducted from the first through the 3rd year of the COVID pandemic that identified conspiracy mindset as an important source of vaccination resistance in the United States (US). We show that the mindset was highly related to the acceptance of misinformation about the safety and efficacy of vaccination, including the vaccines against COVID-19. We show that its effects were overcome to some extent in racial-ethnic and political groups that were likely to have received supportive information from sources trusted within their group. At the same time, some of our evidence suggests that media sources that promoted conspiracy theories about vaccination and the pandemic likely intensified conspiracy mindsets and with it, vaccination resistance. Our findings suggest that efforts countering misinformation cannot rely on simply correcting falsehoods but should also involve engaging trusted leaders who can reassure the conspiracy minded that the recommended action is safe and effective.